Does Banking Employees’ Mental Health Affect their Creativity? - Abdullah, Nor Hazana; Ahmad Sabri, Nur Izzati (Research in Management of Technology and Business, 2022)
Nowadays, the success of organizations depends on employees’ creativity to spur innovation. Employees’ creativity will help an organization to achieve their competitive advantages and sustainability. Banking sector is an economic sector that has been dedicated to holding financial assets for others and also investing those financial assets in order to generate more wealth. Banking sector is heavily invested in technologies and focus on optimizing customer services. Thus, banking employees’ creativity will influence the changes in an organization in order to pursuit success. At present, studies on the impact of mental health on creativity have been lacking, especially in the banking industry. Thus, this study aimed to examine the relationship between mental health and employees’ creativity among bank employees’ at selected premier banks. This study adopted quantitative method as research strategy and questionnaire as a research instrument. A total of 114 questionnaires were collected from the banking employees’ located in Pahang, Johor and Kuala Lumpur. Non-probability sampling technique which is convenience sampling was used to select respondents. The findings showed that there is a positive relationship between mental health and its components with employees’ creativity. These findings provide an understanding about the mental health of the employees and its components impacts on the employees’ creativity.